Trans-cinnamaldehyde-related overproduction of benzoic acid and oxidative stress on Arabidopsis thaliana - López-González, David; Ferradás, Yolanda; Araniti, Fabrizio; Graña, Elisa; Hermida-Ramón, José M.; González, María Victoria; Teijeira, Marta; Rey, Manuel; Reigosa, Manuel J.; Sánchez-Moreiras, Adela M. (Frontiers in Plant Science, 2023)
Trans-cinnamaldehyde is a specialised metabolite that naturally occurs in plants of the Lauraceae family. This study focused on the phytotoxic effects of this compound on the morphology and metabolism of Arabidopsis thaliana seedlings. The addition of the compound caused an increase in benzoic, salicylic and indoleacetic acid content, which is related to the increased gene expression of the aldehyde dehydrogenase enzymes that can drive the conversion of trans-cinnamaldehyde to cinnamic acid. The enzyme-compound interaction was shown to be stable over time by docking and molecular dynamics assays. The hormonal imbalance caused by the action of aldehyde dehydrogenases would be the cause of the oxidative stress symptoms observed in the treated seedlings (increased superoxide and hydrogen peroxide contents, mitochondrial malfunction, and changes in morphology), leading to growth and development inhibition of the trans-cinnamaldehyde -treated seedlings.